UJI AKTIFITAS ANTIBAKTERI EKSTRAK ETANOL KULIT BUAH MANGGIS (Gracinia mangostana L.) TERHADAP PERTUMBUHAN BAKTERI Escherichia coli - Permata, Putri; Kawuri, Retno; Darmadi, AA Ketut (SIMBIOSIS, 2018)
Mangosteen rind has a benefical compounds liked xanthone which consisting of mangostin, mangosterol, mangostinon A and B, trapezifolixanthone, tovophyllin B, alpha and beta mangostin, garcinon B, mangostanol, gartanin, and flavonoid epikatekin that known contain an antibacterial and antidiare agent. Escherichia coli is an opportunistic bacterium that is commonly found in the human colon as a normal flora. Its unique because it can cause primary infection in the intestine such as diarrhea in children, as well as its ability to cause infection in other body tissues outside the intestine.This research was done from December 2016 to March 2017. The methods that used in this research were well diffusion test to know the inhibitory power by measuring the clear zone formed. measure the clear zone of mangosteen rind against Escherichia coli . Then to testing extract compounds, there was used phytochemicals screening test. Data there has been found will be analyzed through analysis of variance (ANOVA). In the inhibitory test of ethanol extract from mangosteen rind ( G. mangostana L. ), it was so effective to inhibit the growth of Escherichia coli through in-vitro test with a resistivity of 1,58 cm and categorized as a strong inhibitory, which MIC from mangosteen rind against Escherichia coli was 3,9% and the compounds that contain in ethanol extract from mangosteen rind ( G. mangostana L . ) were alkaloid, phenolik, flavonoid, saponin and terpenoid. Key word : antibacterial activity, Garcinia mangostana L. , Escherichia coli.